1985
DOI: 10.1007/bf02424463
|View full text |Cite
|
Sign up to set email alerts
|

Change of the crossing-over frequency inDrosophila during selection for resistance to temperature fluctuations

Abstract: Significant differences among cage populations of Drosophila in the dynamics of linkage disequilibrium for marker loci b. cn and vg of chromosome 2 have been found at optimum and extreme temperatures. Fifteen generations of selection under extreme conditions considerably increased recombination frequency in the cn-vg region and over the whole of the b-vg interval. From the data obtained it is inferred that recombination--promoting alleles with intermediate expression in the heterozygous state are responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…Selection for negative geotaxis did not result in if changes in chromosome 2 whereas selection in the opposite direction caused nearly a fourfold increase in if in the b-cn segment and a significant, albeit not as high, increase in the adjacent regions, al-b and cn-vg. A marked if-response of the bcn segment was also observed in our previous experiments with selection for Drosophila thermal adaptation (Zhuchenko et al, 1983(Zhuchenko et al, , 1985Gorodetsky etal., 1990;Korol eta!., 1990).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Selection for negative geotaxis did not result in if changes in chromosome 2 whereas selection in the opposite direction caused nearly a fourfold increase in if in the b-cn segment and a significant, albeit not as high, increase in the adjacent regions, al-b and cn-vg. A marked if-response of the bcn segment was also observed in our previous experiments with selection for Drosophila thermal adaptation (Zhuchenko et al, 1983(Zhuchenko et al, , 1985Gorodetsky etal., 1990;Korol eta!., 1990).…”
Section: Resultssupporting
confidence: 79%
“…Presumably, this difference reflects the reaction of the rec-systems of domesticated species to the long-term pressure of artificial selection. In a series of reproducible experiments, we have shown that adaptation of large cage populations of D. inelanogaster to daily temperature fluctuations (with the amplitude increasing over generations) results in increased recombination (Zhuchenko et a!., 1983(Zhuchenko et a!., , 1985Gorodetsky et a!., 1990;Korol eta!., 1990).…”
Section: Introductionmentioning
confidence: 99%
“…However, changes in recombination rate have been also shown to evolve as a correlated response to artificial selection on other characters (Flexon and Rodell ; Zhuchenko et al. ; Korol and Iliadi ; Rodell et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…This has been verified in a number of empirical studies (eg Harinarayana and Murty, 1971;Flexon and Rodell, 1982;Zhuchenko et al, 1985;Burt and Bell, 1987;Wolf et al, 1987;Korol and Iliadi, 1994). The reverse predictionthat is that manipulating the level of recombination should result in changes in the response to selectionhas received some attention to date, with contradictory results (Carson, 1958;McPhee and Robertson, 1970;Markow, 1975;Malmberg, 1977;Thompson, 1977;Zeyl and Bell, 1997;Rice and Chippendale, 2001).…”
Section: Introductionmentioning
confidence: 88%